Profil Hematologi pada Bayi Baru Lahir dari Ibu Suspek Covid-19 di RSD Idaman Banjarbaru Tahun 2020-2021 - Ellen Jovita Tjitradi; Harapan Parlindungan Ringoringo; Roselina Panghiyangani; Edi Hartoyo; Rahmiati Rahmiati (Homeostasis, 2022)
Abstract: Coronavirus Disease 2019 (COVID-19) is a disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and it is highly contagious. This study aims to determine the hematological profile which includes erythrocytes (RBC), RDW, Hb, hematocrit, MCV, MCH, MCHC, leukocytes (leukocyte differential Count: basophils, eosinophils, neutrophils, lymphocytes, monocytes), platelets, and NLR in newborns from mothers with suspected COVID-19 at the Idaman Hospital Banjarbaru 2020-2021. This research method is descriptive retrospective with data collection through patient medical records. The sampling technique is purposive sampling. In this study, a total sample of 83 neonates from pregnant women with suspected COVID-19 was obtained. However, from the 83 sample, the sample that has hematological profile data and meets the criteria is 69 sample. The results showed that 42 neonates (62,69%) with reactive IgM tests, and 51 neonates (76,12%) with nonreactive IgG tests. In the distribution of the hematological profile of newborns from mothers with suspected COVID-19, found an increase NLR in 33 neonates (47,83%), an increase hemoglobin in 8 neonates (11,59%), an increase hematocrit in 10 neonates (14,49%), an increase MCV in 8 neonates (11,59%), and decrease MCHC in 8 neonates (11,59%). Keywords: hematology profile, newborns, suspected COVID-19 Abstrak: Coronavirus Disease 2019 (COVID-19) adalah penyakit yang disebabkan oleh virus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) dan sangat menular. Penelitian ini bertujuan untuk mengetahui profil hematologi yang meliputi eritrosit (RBC), RDW, Hb, hematokrit, MCV, MCH, MCHC, leukosit (hitung jenis : basofil, eosinofil, neutrofil, limfosit, monosit), trombosit, dan NLR pada bayi baru lahir dari ibu suspek COVID-19 di RSD Idaman Banjarbaru Tahun 2020-2021. Metode penelitian ini adalah deskriptif retrospektif dengan pengambilan data melalui rekam medis pasien. Teknik pengambilan sampel adalah purposive sampling. Dalam penelitian ini didapatkan total sampel 83 neonatus dari ibu hamil dengan suspek COVID-19. Namun, dari 83 sampel tersebut, sampel yang memiliki data profil hematologi dan memenuhi kriteria berjumlah 69 sampel. Hasil penelitian menunjukkan pada pemeriksaan rapid test IgM neonatus ditemukan hasil reaktif sebanyak 42 neonatus (62,69%) dan rapid test IgG ditemukan hasil non reaktif sebanyak 51 neonatus (76,12%). Distribusi profil hematologi bayi baru lahir dari ibu suspek COVID-19 ditemukan peningkatan NLR sebanyak 33 neonatus (47,83%), peningkatan hemoglobin sebanyak 8 neonatus (11,59%), peningkatan hematokrit sebanyak 10 neonatus (14,49%), peningkatan MCV sebanyak 8 neonatus (11,59%), dan penurunan MCHC sebanyak 8 neonatus (11,59%). Kata-kata kunci: profil hematologi, bayi baru lahir, suspek COVID-19